PEMIKIRAN EKONOMI ISLAM MUHAMMAD BÄ€QIR SADR - Harun, Ubay (State Institute of Islamic Studies (IAIN) Palu, 2005)
Muhammad Baqir Sadr serves as a 20th centuryÂ expertÂ in Islamic economics. He combines his thought on Islamic economics with theological-normative and sociological-empirical aspects. This combination of the two approaches can be seen in his thought on economic base, economic principles, economic distribution on pra and pasca-production and theory on production and the role of the state economic affairs.